Efficacy of PD-1/PD-L1 Inhibitors versus Chemotherapy in Lung Cancer with Brain Metastases: A Systematic Review and Meta-Analysis. (20th May 2022) - Yang, Xiaojun; Zeng, Yihong; Tan, Qinquan; Huang, Zhihua; Jia, Jun; Jiang, Guanming
Abstract : Immune checkpoint inhibitors (ICIs) are widely used to treat local or metastatic lung cancer. However, the efficacy of ICI in patients with brain metastases (BM) from lung cancer is unknown. This study aimed to evaluate the efficacy of PD-1/PD-L1 ICIs compared with chemotherapy for patients with lung cancer with BM. Electronic databases (PubMed, Embase, The Cochrane Library, and Web of Science) were searched. The meta-analysis assessed overall survival (OS) and progression-free survival (PFS) of the PD-1/PD-L1 inhibitors axis and its relationship with pathological type, drug modality, and the treatment line number in patients with BM from lung cancer. We included 694 patients with BM from lung cancer from 11 randomized controlled trials. Statistical analysis showed that compared with chemotherapy, PD-1/PD-L1 inhibitors could significantly prolong OS (hazard   ratio   HR = 0.75, 95 % confidence   interval   95 % CI = 0.51 – 0.99 ) and PFS (HR = 0.65, 95 % CI = 0.51 – 0.80 ). In the subgroup analysis, ICIs plus chemotherapy improved PFS (HR = 0.60, 95 % CI = 0.40 – 0.80 ), but not OS (HR = 0.75, 95 % CI = 0.30 – 1.19 ). The efficacy of ICI monotherapy in patients with BM was significantly different between OS and PFS: OS pooled HR = 0.81 (95 % CI = 0.57 – 1.05 ) and PFS = 0.78 (95 % CI = 0.62 – 0.94 ). Among different pathological types, the OS pooled HR was 0.67 (95 % CI = 0.39 – 0.95 ) for non-small cell lung cancer (NSCLC) and 0.94 (95 % CI = 0.56 – 1.33 ) for small cell lung cancer (SCLC); the PFS pooled HR was 0.58 (95 % CI = 0.39 – 0.76 ) for NSCLC and 0.79 (95 % CI = 0.65 – 0.93 ) for SCLC. Subgroups analysis of treatment line showed that no advantage for OS with ICIs as first-line or subsequent-line therapy, whereas ICIs as first-line (HR = 0.63, 95 % CI = 0.53 – 0.74 ) and second-line (HR = 0.62, 95 % CI = 0.62 – 0.96 ) benefitted PFS. This meta-analysis implied that compared with chemotherapy, PD-1/PD-L1 inhibitors significantly improved efficacy treatment of patients with BM from lung cancer. Further studies are needed to confirm the role of ICIs in different pathological types and drug treatment modalities.